ЖАСЛАР МИЛЛИЙ МЕНТАЛИТЕТИН ҚӘЛИПЛЕСТИРИЎДЕ ХАЛЫҚ ДАНАЛЫҒЫНАН ПАЙДАЛАНЫЎ – ФИЛОСОФИЯЛЫҚ ТӘРБИЯНЫҢ ТИЙКАРЫ - Усенов, Ж.У. (FAN va JAMIYAT, 2019)
In the article the author shows the place and role of wisdom, folklore and artistic literary heritage in the formation of national mentality of the youth. There are the new tasks to study the historical and national values of the Karakalpak people. The article also contains some important points of view about traditions and customs, ethnic history and ethnogenesis of the ancient statehood of the Karakalpak people. The article also contains some important points of view about traditions and customs, ethnic history and ethnogenesis of the ancient statehood of the Karakalpak people.